2019
DOI: 10.1021/acs.jpca.9b10779
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Dimerization by Organic Radical Reactions during Heterogeneous Oxidative Aging of Oxygenated Organic Aerosols

Abstract: Oxidative aging of atmospheric organic aerosols (OA) substantially modifies their chemical compositions, physical properties, and hence the various environmental impacts. Here, we report observations of a previously unrecognized process leading to dimer formation during heterogeneous •OH-initiated oxidative aging of oxygenated OA. Isomer-resolved ion mobility mass spectrometry measurements and reaction-diffusion kinetic simulations are in good agreement, elucidating new mechanisms of dimerization by organic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(94 citation statements)
references
References 80 publications
6
83
0
Order By: Relevance
“…This technique is increasingly used in the structural characterisation of small molecules since the introduction of the first commercial IMS-TOFMS in 2006 [9]. In the field of atmospheric science, IMS-TOFMS is successfully used for the molecular characterisation of β-pinene originating organosulfates [10], isoprene originating organosulfates [11], aerosol bound alkyl nitrates [12], classification of atmospherically relevant organic compounds [13], aqueous phase oligomerisation of α,β-unsaturated carbonyls and acids [14], separation of highly oxygenated molecules in laboratory-generated α-pinene SOA [15], particle-phase reaction products of α-pinene oxidation [16], and heterogeneous oxidation of organic aerosols [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is increasingly used in the structural characterisation of small molecules since the introduction of the first commercial IMS-TOFMS in 2006 [9]. In the field of atmospheric science, IMS-TOFMS is successfully used for the molecular characterisation of β-pinene originating organosulfates [10], isoprene originating organosulfates [11], aerosol bound alkyl nitrates [12], classification of atmospherically relevant organic compounds [13], aqueous phase oligomerisation of α,β-unsaturated carbonyls and acids [14], separation of highly oxygenated molecules in laboratory-generated α-pinene SOA [15], particle-phase reaction products of α-pinene oxidation [16], and heterogeneous oxidation of organic aerosols [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…These include particle-phase esterification of carboxylic acids such as cis-pinic acid and terpenylic acid leading to Mw 358 [21], a gas phase mechanism involving Criegee intermediates [23], and the formation of RO 3 R' from the reaction of RO 2 • and R'O•, and the subsequent decomposition of acyl hydroperoxide groups to form stable esters [19]. Other suggested mechanisms that can lead to dimeric SOA compounds that are not exclusive to Mw 358 and Mw 368 include heterogeneous reactions of aldehydes with hydroperoxides [27,28], and more recently a series of organic peroxy and alkoxy radical cross-reactions at the interface forming dimeric compounds [17]. Recent mass spectrometric studies on α-pinene SOA showed that these dimers consist of diaterpenylic acid and cis-pinic acid for Mw 358 [19][20][21] and of cis-hydroxyl pinonic acid and cis-pinic acid for Mw 368 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Their fraction is estimated to be 96.4% from the sum of deprotonated monomers (70.2%) and product ions with a lower m/z value (26.2%). It is known that for API‐MS, HB clusters are easily generated as instrumental artifacts . In this study, ions and neutral species in the ambient discharge area, which are related to α‐pinene oxidation products and air constituents, are introduced into the first differential pumping region of the mass spectrometer at ca.…”
Section: Resultsmentioning
confidence: 99%
“…To accurately determine these properties, we need to know the fraction of ion signal that originates from the abovementioned mechanisms (a) or (b). Furthermore, when using API‐MS, the formation of hydrogen‐bonded dimers as instrumental artifacts should be taken into consideration owing to various ionization processes and/or adiabatic expansion caused by the pressure difference between the ambient ionization area and the vacuum region in MS . The fractions of these artifacts should be subtracted from the detected ion signals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation